The effect of forensic accounting techniques and skills on detecting and combating financial corruption - Subhi Mohamed Saleh; Zubir Azhar; Bayan Sedeeq Azeez (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This paper aims to identify the effect of forensic accounting techniques in detecting (and preventing) corruption and fraud and identify the skills that required for Forensic Accountants in detection and combating the practices of corruption and financial fraud. To achieve the objectives of the study was developed questionnaire included (22 questions) distributed on 63 professionals accounting (external auditors) in the Kurdistan Region Iraq, The researchers reached a number of conclusions after analyzing questionnaire’s questions. The most important of these conclusions is that the Using Forensic Accounting techniques that have an impact in detecting and combating financial corruption. The researchers also made a number of recommendations, Educating accountants and auditors in the Kurdistan Region with Forensic Accounting and the necessary skills to practice them, through holding training courses and workshops, which inform them about techniques and skills Forensic Accounting and its goals.